The bell bandit - Davies, Jacqueline, 1962- (Davies, Jacqueline, 1962- Lemonade war series, 2012)
Jessie and Evan have always spent New Year's Eve at Grandma's house listening to the New Year's bell toll, but this year is different because Grandma's house burned down and the New Year's bell has gone missing. As they search for the missing bell, they realize that something is different about Grandma.